2014
DOI: 10.9790/1684-11612736
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of tuber movement during mechanical peeling of cassava

Abstract: Cassava Peeling has been identified as the only un-mechanized unit operation in cassava production which has constituted global challenge in twenty-first century despite an ever-increasing demand for the crop. As at today, cassava peeling is still largely carried out manually, it makes the process to be slow, labour intensive, arduous in nature, and low productivity. This research work aimed to analyse and model tuber movement during mechanical peeling. Preliminary experiment was carried out on newly harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Generally, throughput capacity has been reported to increase with an increase in both speed of operation and tuber loading (Adekunle et al, 2018;Alhassan et al, 2018;Olukunle and Akinnuli, 2012). Jimoh et al (2016) also reported that throughput capacity increased with an increase in speed and weight of cassava peeled for both serrated and smooth-edged knife peeling machines. The reason for this pattern is that, since throughput capacity is a function of the weight of cassava and peeling time, increasing the tuber loading or reducing the peeling time (which can be achieved by increasing the speed, especially in continuous peelers) will increase the throughput capacity (Jimoh et al, 2016).…”
Section: Throughput Capacitymentioning
confidence: 88%
See 4 more Smart Citations
“…Generally, throughput capacity has been reported to increase with an increase in both speed of operation and tuber loading (Adekunle et al, 2018;Alhassan et al, 2018;Olukunle and Akinnuli, 2012). Jimoh et al (2016) also reported that throughput capacity increased with an increase in speed and weight of cassava peeled for both serrated and smooth-edged knife peeling machines. The reason for this pattern is that, since throughput capacity is a function of the weight of cassava and peeling time, increasing the tuber loading or reducing the peeling time (which can be achieved by increasing the speed, especially in continuous peelers) will increase the throughput capacity (Jimoh et al, 2016).…”
Section: Throughput Capacitymentioning
confidence: 88%
“…Jimoh et al (2016) also reported that throughput capacity increased with an increase in speed and weight of cassava peeled for both serrated and smooth-edged knife peeling machines. The reason for this pattern is that, since throughput capacity is a function of the weight of cassava and peeling time, increasing the tuber loading or reducing the peeling time (which can be achieved by increasing the speed, especially in continuous peelers) will increase the throughput capacity (Jimoh et al, 2016). Concerning the size of cassava roots, Olukunle and Akinnuli (2012) reported that throughput capacity increases with an increase in size while Jimoh et al (2014) stated that the size of roots is inversely proportional to peeling time (which is inversely proportional to throughput capacity).…”
Section: Throughput Capacitymentioning
confidence: 88%
See 3 more Smart Citations